Human dignity and HIV / AIDS - Bouwer, Johan (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2007)
The HI virus speaks to people across national boundaries and evokes different reactions. In this article an analysis is made of the place awarded to the notion of "human dignity" in the religion-HIV / AIDS discourse and differences in perspective on "human dignity" as possible grounding principle for this discourse in both African and Western contexts. In Africa this is related to the notion of the imago Dei and in the West to the notion of the imago hominis. Because of the danger of "human dignity", given its foundational position in international charters and jurisdiction, becoming an empty concept, it is contended that the concept of "honour", which actually encompasses that of "dignity" and its necessary counterpart, self-respect, might offer a common basis for a religious discourse uniting Africa and the West in finding a common language that will help people to not only escape the stigma, but also to act upon the need for the eradication of this pandemic. In this discourse God is seen as a friend who has compassion, shows respect for human beings, is trustworthy and non-judgemental and is One who cares unconditionally.
Free